ANALISIS KEBUTUHAN PELATIHAN SUMBER DAYA MANUSIA DALAM RANGKA JOB ROTATION UNTUK MENINGKATKAN KINERJA KARYAWAN PENDAHULUAN PADA AUTO 2000 DENPASAR - I Wayan Putrana; Putu Adi Prayustika; Putu Diana Permana Putri (STIMI Handayani Denpasar, 2020)
This study discusses the analysis of human resource training needs in the context of job rotation to improve employee performance in auto2000 Denpasar. The purpose of this study is that later the company can provide policies to provide human resource training for employees who will be rotated so can later provide good performance for the company. This study uses data analysis techniques such as Training Need Analysis (TNA) which are divided into several levels including organizational analysis, task analysis, and individual analysis. In the individual analysis used assessment indicators given to administrative employees who have been rotated with a total of 20 employees. From the results that have been obtained it is stated that the employees of the Auto 2000 Denpasar administration require intense training before holding a job rotation from the calculations obtained through individual analysis assessment indicators obtained an average of 43.06% included in the must know category with the average category lowest of 0-50% which means that employees really must be considered and must know the capabilities possessed by these employees. From these results it is possible to determine the training needed by providing job instruction learning, coaching, and temporary assignments.